HUBUNGAN NEURON SPECIFIC ENOLASE (NSE) SERUM DENGAN DEFISIT NEUROLOGIS STROKE INFARK - , dr. Noor Kamariah; , dr. Setyawati, Sp.PK(K). ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Ischemic stroke is a leading cause of death and disability in the world. The management of stroke is determined by the diagnosis and prognosis that will happen and the assessments is based on clinical examination and work up studies. Analysis of serum biomarker to monitor the central nervous system tissue damage in subclinical level is urgently needed. Among those monitors detects the specific proteins or enzymes derived from astroglia and neuronal cells in the peripheral blood. One of the proposed biomarker is a Neuron specific Enolase (NSE) which is believed to have a positive correlation with the severity of ischemic stroke. The objective of this study is to test the relationship between serum NSE levels with neurologic deficits in ischemic stroke. This is a hospital-based cross sectional study, which assess the relationship between serum NSE levels with neurological deficits in ischemic stroke. The assessment of neurological deficits in this study is done by Skala Stroke Gadjah Mada (SSGM, Gadjah Mada University Stroke Scale). the target population is all patients with acute ischemic stroke â¥ 24 hours after onset who were treated at Dr Sardjito Hospital, Yogyakarta. The reachable population is ischemic stroke patients treated in the Stroke Unit of Dr Sardjito hospital, Yogyakarta. The study sample is new consecutive patients who were treated at the Stroke Unit of Dr Sardjito hospital Yogyakarta, diagnosed with acute ischemic stroke based on Head CT scan between the September and December 2010. serum NSE will be measured with a sandwich ElectroCheluminescence immunoassay (ECLIA) method with a Cobas e 411 instrument. The data characteristics will be presented as the result of descriptive analysis. To find any correlation between serum NSE levels and SSGM score as well as infarct volume in all subjects, we will use Pearson correlation analysis if data has a normal distribution or the alternative Spearman correlation for skewed data. Normality of data distribution will be assessed by Kolmogorov Smirnov test, with p value <0.05. Statistical analysis will be conducted with significance cut off of p<0.05 and 95% confidence interval. The results of this study are expected to show a significant correlation between serum NSE levels with neurologic deficits of ischemis stroke.